전자선을 이용한 질소산화물 저감 공정에서 배기가스 내 산소 농도의 영향 - 손지은(Jieun Son); 조상희(Sang-Hee Jo); 오용환(Yong-Hwan Oh); 김태훈(Tae-Hun Kim); 이용재(Yongjae Lee) (한국대기환경학회지(국문), 2024)
Electron beam flue gas treatment (EBFGT) has garnered attention as an effective method for the removal of nitrogen oxides (NOx), offering advantages in low energy consumption and high removal capacity. Numerous studies have explored the electron beam process for NOx treatment using aqueous additives, predominantly focusing on flue gases from coal-fired combustion, characterized by high NOx concentrations. Recently, the application of this technology has expanded to industries with lower NOx emissions, such as the steel, petrochemical, and semiconductor sectors, driven by stringent emission regulations. Typically, these industrial flue gases exhibit a unique characteristic of having lower oxygen content compared to atmospheric air, attributed to the combustion-based treatment processes. In this context, our study investigated the impact of oxygen concentration on NOx removal efficacy using the EBFGT approach, particularly under conditions of low NOx concentration. The electron beam process was established with a simultaneous injection of sodium hydroxide solution as an additive and 30, 60, and 100 ppm of NOx was treated. The oxygen concentration in background gas was varied from 21 to 10 vol.% to evaluate its effect on NOx removal. When the oxygen level in background gas was reduced from 21 to 10 vol.%, the removal efficiency of NOx was increased to 3.9%p on average under optimized operating parameters (e.g. absorbed dose and flow rate of the additive solution). This phenomenon implies that the oxidation of nitric oxide (NO) and nitrogen (N2) to generate nitrogen dioxide (NO2) seems to be suppressed under low-oxygen environment and thus improves NO2 removal. While further research is necessary to enhance the system’s capacity and efficiency, these findings distinctly indicate the potential of the electron beam treatment system for NOx removal in industrial applications. KCI Citation Count: 0